The west passage - Pechaček, Jared (Tordotcom, Tor Publishing Group, 2024)
"When the Guardian of the West Passage died in her bed, the women of Grey Tower fed her to the crows and went back to their chores. No successor was named as Guardian, no one took up the fallen blade; the West Passage went unguarded. Now, snow blankets Grey in the height of summer. Rats erupt from beneath the earth, fleeing that which comes. Crops fail. Hunger looms. And none stand ready to face the Beast, stirring beneath the poisoned soil. The fate of all who live in the palace hangs on narrow shoulders. The too-young Mother of Grey House sets out to fix the seasons. The unnamed apprentice of the deceased Grey Guardian goes to warn Black Tower. Both their paths cross the West Passage, the ancient byway of the Beast. On their journeys they will meet schoolteachers and beekeepers, miracles and monsters, and very, very big Ladies. None can say if they'll reach their destinations, but one thing is for sure: the world is about to change"--